Avian myeloblastosis virus and E26 virus oncogene products are nuclear proteins. - Boyle, W J (1984)
The defective acute leukemia viruses avian myeloblastosis virus (AMV) and E26 virus each contain an inserted cellular sequence related to the same highly conserved cellular gene, proto-amv. The oncogenes of these two retroviruses differ from this cellular proto-oncogene in gene structure, transcript structure, and gene product. The product of the AMV oncogene (myb) is a 48,000 Mr protein, p48myb, encoded by a transduced segment (amv) of proto-amv flanked by short helper-virus-derived terminal sequences. The E26 virus oncogene product is a 135,000 Mr protein, p135gag-amve-ets, encoded by significant portions of a viral structural gene (gag), sequences related to proto-amv (amve), and additional E26-specific sequences (ets) transduced from cellular proto-ets. Both p48myb and p135gag-amve-ets transforming proteins are located in the nucleus of cells transformed by these viruses. A protein of 110,000 Mr which is specifically immunoprecipitated by antisera to amv peptides and may be the product of the normal cellular gene (proto-amv) has been located in the cytoplasm of cells that express proto-amv mRNA.